Characteristics of Briquettes Produced from Rubber Seed Shell and Palm Kernel Shell Using Tapioca Flour as Binder - Farid Jayadi; Devia Gahana Cindi Alfian; Muhammad Hasbi Pratama; Fajar Perdana Nurullah; Dicky Januarizky Silitonga; Lathifa Putri Afisna (TURBO [Tulisan Riset Berbasis Online], 2025)
Indonesia faces challenges in managing renewable energy as an alternative to fossil fuels. This study aims to compare commercially available briquettes with experimental briquettes produced from a mixture of rubber seed shells and palm shells using tapioca flour as a binder. The raw material composition variations between rubber seed shells and palm shells used were 80:20, 50:50, and 20:80, with 10% tapioca flour binder, and dried at a temperature of 100Â°C for 3 hours. The purpose of this research is to compare the produced briquettes with those already marketed. Based on the experiments and tests carried out, the results show that the 20:80 variation produced briquettes most comparable to the market samples, with a density of 0.7438 g/cmÂ³, moisture content of 3.43%, calorific value of 6849.46 cal/gram, combustion rate of 0.1117 g/minute, and a drop test value of 4.7672%.